Diversity of Cellulose hydrolyzing bacteria from the Gut of Coptotermes Heimi (Rhinotermitidae) - Kakkar, Nidhi; Gupta, Sanjeev K.; Bura, Aman; Gandhi, Aastha (Asian Journal of Biological and Life Sciences, 2018)
This study was aimed to investigate the cellulolytic bacteria of termite gut symbionts of worker Coptotermes heimi (Wasmann) and to identify bacteria with the ability to degrade the cellulosic biomass to glucose monomers. These bacterial isolates were checked for cellulolytic activity on CMC agar by staining with Gram’s Iodine. The bacteria were identified on the basis of their morphology like shape and colour of the colony, Gram’s staining and KOH test. The Biochemical analysis was done by performing different tests (Citrate Utilization, Cellulase activity, Starch hydrolysis, EMB, MacConkey, Mannitol Salt agar, TSI, MR, Nitrate test etc.) and molecular characterization was done by using bacterial 16S primers to amplify the 16SrRNA gene. The culturable isolates obtained from the termite guts were: Bacillus atrophaeus, B. pumilus, B. licheniformis, B. amyloliquefaciens, B. coagulans, B. megaterium and B. cereus. All these isolates were rod shaped Bacilli, Gram positive, KOH negative. B.pumilus showed maximum cellulolytic index (0.69). B.cereus was cellulase negative. The study suggested that the termite guts are an important source for the study of bacteria and bacterial enzymes benefit for biotechnology. These guts can be utilized for microbiological, genetic, agricultural and industrial applications.
Keywords: 16SrRNA; Bacilli; cellulase; Coptotermes heimi; KOH test; Termite